Scale development : theory and applications - DeVellis, Robert F. (Thousand Oaks, Calif. : SAGE Publications, 2003)
"A best-seller in the first edition, Scale Development: Theory and Applications, Second Edition has been extensively updated and revised to address changes in the field and topics that have grown in importance since the first edition. Widely adopted for graduate courses in departments such as Psychology, Public Health, Marketing, Nursing, and Education, this book will prove beneficial to applied researchers across the social sciences."--BOOK JACKET.
1. Overview -- 2. Understanding the Latent Variable -- 3. Reliability -- 4. Validity -- 5. Guidelines in Scale Development -- 6. Factor Analysis -- 7. An Overview of Item Response Theory -- 8. Measurement in the Broader Research Context.
Includes bibliographical references and index (p. 161-165) and index.
Keywords: Scaling (Social sciences); Social Sciences